PENGARUH MARKETING PUBLIC RELATIONS, BRAND RELATIONS, SERVICE QUALITY TERHADAP KEPUTUSAN PASIEN BEROBAT PADA SILOAM HOSPITAL - Sarwo Eddi Wibowo (LPPM University 17 Agustus 1945 Samarinda, 2017)
Marketing Communication will be variety aspect about consumer, marketing concept, brand relations marketing, value of marketing, and integrated marketing communication (advertising, promotion, public relations, personal selling, direct marketing, integrated marketing communications). My research, researcher many experience about marketing communication including marketing public relations, brand relations, service quality, and result consumer in service quality Researcher very interested and critical thinking about research Marketing communication including Marketing Public Relations, Brand Relations, Service Quality and result consumer in Siloam Hospital. In research have quantitative method and hypothesis test in any variable. (X1): Marketing Public relations (include indicator publication, media identity, activities, speech, and public service. (X2): Brand Relations include intimate, interdependence, quality of brand, connection, and trust. (X3: Service Quality include reliability, responsiveness, assurance, emphaty, and tangible. (Y): identification, search of information, evaluation alternative, judgment, purchases intention. Result consideration F (simultan) indicate exist influence of significant between variable Marketing Public Relations, Brand Relations, and Service Quality toward judgment consumer about consumer judgment in Siloam Hospital. Result of analyze T (partial) refer that variable Marketing Public Relations, Brand Relations, and Service Quality influent significant to consumer judgment in Siloam Hospital.